Asymmetries in Ground Reaction Forces During Turns by Elite Slalom Alpine Skiers Are Not Related to Asymmetries in Muscular Strength - Ogrin, Jan; Šarabon, Nejc; Madsen, Mads Kjær; Kersting, Uwe; Holmberg, Hans-Christer; Supej, Matej (Frontiers in Physiology, 2021)
The ground reaction forces (GRF) associated with competitive alpine skiing, which are relatively large, might be asymmetric during left and right turns due to asymmetries in the strength of the legs and torso and the present investigation was designed to evaluate this possibility. While skiing a symmetrical, 20-gate slalom course, the asymmetries of 9 elite alpine skiers were calculated on the basis of measurements provided by inertial motion units (IMU), a Global Navigation Satellite System and pressure insoles. In addition, specialized dynamometers were utilized to assess potential asymmetry in the strength of their legs and torso in the laboratory. In total, seven variables related to GRF were assessed on-snow and eight related to strength of the legs and torso in the laboratory. The asymmetries in these parameters between left and right turns on snow were expressed in terms of the symmetry (SI) and Jaccard indices (JI), while the asymmetries between the left and right sides of the body in the case of the laboratory measurements were expressed as the SIs. The three hypotheses to be tested were examined using multivariable regression models. Our findings resulted in rejection of all three hypotheses: The asymmetries in total GRF (H1), as well as in the GRF acting on the inside and outside legs (H2) and on the rear- and forefeet GRF (H3) during left and right turns were not associated with asymmetries in parameters related to muscular strength. Nevertheless, this group of elite slalom skiers exhibited significant asymmetry between their right and left legs with respect to MVC during ankle flexion (0.53±0.06 versus 0.60±0.07 Nm/kg, respectively) and hip extension (2.68±0.39 versus 2.17±0.26 Nm/kg), as well as with respect to the GRFs on the inside leg while skiing (66.8±7.39 versus 76.0±10.0 %BW). As indicated by the JI values, there were also large asymmetries related to GRF as measured by pressure insoles (range: 42.7 – 56.0%). In conclusion, inter-limb asymmetries in GRFs during elite alpine skiing are not related to corresponding asymmetries in muscular strength. Although our elite athletes exhibited relatively small inter-limb asymmetries in strength, their asymmetries in GRF on-snow were relatively large.